Morphological analysis of biofilm of peritoneal dialysis catheter in refractory peritonitis patient - Kusaba, Tetsuro (CEN Case Rep, 2012)
A 66-year-old man undergoing peritoneal dialysis (PD) was admitted to our hospital for treatment of PD-related peritonitis. Culture of the PD fluid revealed the presence of Citrobacter freundii, and therapy with ceftazidime was started intraperitoneally. The cell count in PD fluid slowly decreased over time during the first 2 weeks of treatment, but increased again on the 14th hospital day. A second culture of the PD fluid revealed the presence of Enterococcus species. A switch in antibiotic therapy to vancomycin did not improve the cell count in the PD fluid. A third culture of the PD fluid revealed the presence of Stenotrophomonas maltophilia. The PD was discontinued and the catheter removed on the 28th hospital day. Examination of the catheter revealed that the inner tip was coated with a fibrous sheet of cells, suggesting biofilm formation. Following catheter removal, the patient was administered intravenous ciprofloxacin, and the inflammatory reaction started to disappear immediately and had completely disappeared after 1 week of treatment. Microscopic analysis of the fibrous structure on the catheter revealed multiple layers of various inflammatory cells. Immunostaining revealed the presence of CD44-positive polynuclear cells, indicating neutrophils, facing the catheter lumen. CD68-positive cells, indicating macrophages, were observed in the following layer, and keratin-positive cells, indicating peritoneal mesothelial cells, were present at the bottom of the structure. Based on the immediate improvement of PD-related peritonitis after catheter removal, we presumed that this biofilm contributed to the intractability of the patient’s peritonitis. Morphological analysis of catheter revealed that both the mesothelial cells and the various inflammatory cells may have contributed to biofilm development.